Effect of Commercial Feed Substitution with BSF Maggot Flour (Hermetia Illucens) on Laying Quail Production Performance - Sadarman, Sadarman; Irawati, Evi; Hidayati, Hidayati; Bahauddyin, Bahauddyin; Pandra, Andika; Qomariyah, Novia; Wahyono, Teguh; Adli, Danung Nur; Irawan, Agung; Rahman, Rahman; Adegbeye, Moyosore Joseph (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This study aims to determine the effect of substituting commercial feed with BSF maggot flour (Hermetia illucens) on the performance and productivity of laying quail. One hundred (100) 20 days-old laying quails with an initial weight of 2.9±8.26 g/head were divided into four treatments with five replicates per treatment using the completely randomized design (CRD). The treatments were T1 (0% BSF maggot flour as control), T2 (1.50% BSF maggot flour and 98.5% commercial feed), T3 (2% BSF maggot flour and 98% commercial feed), and T4 (2.50% BSF maggot flour and 97.5% commercial feed). The parameters measured were feed intake (g/head/mg), the body weight at first egg-laying (g/head), age at first egg-laying (days), the weight of first egg (g/grain), daily egg production (%), quail egg weight (g/item), and feed conversion ratio. The results showed that BSF maggot flour in commercial rations significantly affected feed intake (P<0.05) with a consumption range of 153-154 g/head/week.  However, the provision of BSF maggot flour up to 2.50% of commercial feed had no significant effect (P>0.05) on the body weight at first egg-laying, the age at the first egg laying, the weight of the first egg, daily egg production (%), egg weight (g/grain), and feed conversion ratio. This study shows that substituting 2% maggot BSF flour in commercial rations can increase feed intake and maintain egg production, weight, and conversion. Furthermore, giving BSF maggot flour to a level of 2.50% could not improve the body weight at the first laying of quail and the age at the first egg-laying.Keywords egg weight, feed consumption, feed conversion ratio, BSF maggot